Fuzzy supply chain coordination mechanism with imperfect quality items - Liu, Shukuan; Gao, Jie; Xu, Zeshui (Technological and Economic Development of Economy, 2019)
We study the supply chain (SC) returning strategy and quantity discount coordination under the condition of product quality defects. We assume that the demand is a triangular fuzzy number (TFN), considering the SC coordination problem consisting of a manufacturer and a retailer. The decentralized SC coordination model and the integrated SC coordination model under a fuzzy environment are established respectively. The fuzzy set theory is used to study the manufacturer’s quantity discount and the retailer’s coordination of return policy. The signed distance is used as the ranking method to find the optimal order quantity in SC, and the optimization theory is used to maximize the participants’ profits. We first demonstrate that the retailer’s profit will be reduced in a typical integrated channel, and then we propose a quantitative discount return policy to coordinate the profits of the manufacturer and the retailer. Finally, the coordination steps are designed, and the manufacturer’s return policy is given. Meanwhile, some illustrative cases are provided to illustrate the feasibility of the proposed model.